MARKETING AND ENGINEERING SERVICES AT INDUSTRIAL ENTERPRISES: PROBLEMS AND COLLABORATIVE MECHANISMS - Lidia M. Shcherba (Advanced Engineering Research, 2011)
Communication problems between marketing specialists and engineers at the industrial enterprises are considered. Basic reasons of un-cooperation of marketing and engineering services are revealed. Approaches to implementation of the collaborative activities of the involved subdivisions are offered.